Tectonica do Complexo Varginha na regiao de Sao Joao da Boa Vista (SP) - Morales, N.; Hasui, Y. (My University, 1990)
Migmatites, high-grade gneisses and granitoids represent the most important Precambrian rocks of Sao Joao da Boa Vista region. Structures are interpreted as due to low-angle oblique non-coaxial ductile shear, developed under conditions of amphibolite facies. Transcurrent ductile shear zones and associated drags modify the foliation and lineations orientations. A first phase of migmatization related to anatexis seems to be developed before or early during the thermo-tectonic process. A second one is syntectonic, and represents the main regional phase. Joints and faults represent the brittle features, the faults marked by cataclastic rocks and intense retrometamorphism along the main zones. -from English summary
Tectonics of the Varginha Complex in the Sao Joao da Boa Vista Region, SP
Keywords: ductile shear; metamorphism; migmatization; polyphase deformation; structural framework; tectonics; Brazil, Sao Paulo, Sao Joao da Boa Vista, Varginha Complex